The master and the disciple an early Islamic spiritual dialogue : Arabic edition and English translation of Jaʻfar b. Manṣūr al-Yaman's Kitāb al-ʻĀlim wa'l-ghulām - Jaʻfar ibn Manṣūr al-Yaman 10th cent (Ismaili texts and translations series (Institute of Ismaili Studies), 2001)
This key source for pre-Fatimid Ismaili history includes a fully annotated translation and Arabic critical edition of one of the earliest surviving Ismaili Shi'i writings, Kitåb al-'Ålim wa'l-ghulåm by the Yemeni author Ja'far Ibn Manßúr al-Yaman. The book is unique because it provides the most elaborate example available of the narrated dramatic dialogues form in Arabic literature. It also vividly illustrates the processes by which early esoteric Shi'i ideas and institutions eventually contributed to the evolution of more familiar forms of Sufism in the Islamic West.